Finite element stabilization methods and solvers for heat exchanger applications: a review (2016)
This review focuses on the applications of finite element method (FEM) for heat exchanger analyses. Solutions to convection-dominated heat transfer problems using the Galerkin FEM approximation are always characterised with errors caused by numerical instabilities. Efforts to enhance the stability and exactness of results had led to development of a number of stabilization techniques. Also, there have been algorithms formulated to effectively solve the sparse symmetric and non-symmetric matrix systems resulting from FEM discretised equations of thermal flow problems. The development of stabilization techniques and solvers has made the FEM approach a more formidable computational fluid dynamics (CFD) tool. However, there have been limited uses of finite element CFD codes to heat exchanger applications.